Infrainguinal anastomotic arterial graft infections treated by selective graft preservation. - Calligaro, K D (1992)
The purpose of this study was to determine whether the type of graft material and bacteria involved in an infrainguinal arterial anastomotic infection can be used as guidelines for graft preservation. Between 1972 and 1990, the authors treated 35 anastomotic infections involving a common femoral or distal artery. The graft material was Dacron in 14 patients, polytetrafluoroethylene (PTFE) in 14, and vein in 7. Of the 14 Dacron grafts, immediate graft excision was required for overwhelming infection in eight patients (bleeding in five, sepsis in three) and for an occluded graft in one patient. Three of five patients failed attempted graft preservation because of nonhealing wounds. Thus, 12 of the 14 Dacron grafts ultimately required graft excision. Of the 21 "smooth-walled" vein and PTFE grafts, 10 required immediate graft excision for occluded grafts (five PTFE, one vein) or bleeding (three PTFE, one vein). Ten of the remaining 11 (91%) patients with patent "smooth-walled" grafts, intact anastomoses, and absence of sepsis managed by graft preservation healed their wounds and maintained distal arterial perfusion. Wound cultures grew pure gram-positive cocci in 17 of 21 "smooth-walled" graft infections versus 8 of 14 Dacron graft infections. In the absence of systemic sepsis, graft preservation is the treatment of choice for gram-positive infections involving an intact anastomosis of patent PTFE and vein grafts. Regardless of the bacterial cause, the authors recommend that any infrainguinal anastomotic infection of a Dacron graft be treated by immediate excision of all infected graft material.